Unsteady mixed convection near the forward stagnation point of a two-dimensional symmetric body prescribed with a constant wall heat flux - Roslinda Nazar,; Ioan Pop, (Universiti Kebangsaan Malaysia, 2004)
The unsteady mixed convection boundary layer flow near the forward stagnation point of a two-dimensional symmetric body prescribed by a uniform heat flux rate is studied in this paper. The main aim of the investigation is to identify situations in which dual solutions for the steady-state flow can be determined when the flow is opposing. It is also shown that there is a smooth transition from the unsteady initial flow (short time) to the final steady state flow (large time).